Perbedaan Perilaku Masyarakat dalam Pelaksanaan Nagari Siaga di Nagari Padang Laweh dan Nagari Kubang Putiah Kabupaten Agam - Putri Nilam Sari; Rizanda Machmud; Nopriadi . (STIKes Hang Tuah Pekanbaru, 2012)
The number of Nagari Siaga in West Sumatera Province at the end of the year 2008 is 2.125. However this number has not been reached the target yet that are 3.317 Nagari Siaga. The implementation of Nagari Siaga requires a full support of the community as the major driver that is initiated by the understanding and positive attitude towards health itself. The aim of this research is knowing about the difference of community behaviour in implementating Nagari Siaga between Nagari Padang Laweh and Nagari Kubang Putiah in Agam District. This study used cross sectional study design, with a total sample of 84 head families in both villages. Dependent variable in this study is Nagari Siaga and independent variable are knowledge, attitude and practice. Bivariate analysis was done by Chi Square (X2) with Î± = 0,05. The analysis shows significant relationship between the variables of knowledge and practice on implementation of Nagari Siaga with p value of 0,00. There are differences in knowledge and attitudes between the two villages. Knowledge and community practices in Nagari Kubang Putiah were better than Nagari Padang Laweh. Attitude variables can not be tested because the attitude in both villages is completely (100%) positive. It needs sosialization to the community about the importance of health and Nagari Siaga program in Nagari Padang Laweh, so that the program can be run optimally as well as Nagari Kubang Putiah. For Nagari Kubang Putiah, Nagari Siaga program should be developed continiously. Cross-sector participation should be increased to the success of Nagari Siaga program